2022
DOI: 10.1039/d1ra06480k
|View full text |Cite
|
Sign up to set email alerts
|

A phase conversion method to anchor ZIF-8 onto a PAN nanofiber surface for CO2 capture

Abstract: Poly acryl nitrile (PAN) nanofibers were prepared by electrospinning and coated with zeolitic imidazolate framework-8 (ZIF-8) by a phase conversion growth method and investigated for CO2 capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Li et al reported a phase-inversion method that allowed the growth of ZIF-8 on the surface of electrospun polyacrylonitrile (PAN) nanofibers to be used for CO 2 capture. 208 ZIF-8 was solvothermally synthesized by mixing zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O) and 2-methyl imidazole (2-mim) for 1 h at room temperature; complete physical and chemical analysis of the resulting structures is shown in Table 3. PAN nanofibers were immersed in Zn(NO 3 ) 2 ·6H 2 O for 20 min, and then 2-mim were added and left to react for 30, 60, and 90 min, leading to formation of ZIF-8/PAN-30, ZIF-8/PAN-60, and ZIF-8/PAN-90, respectively.…”
Section: Applications Of Framework For Co2 Detectionmentioning
confidence: 99%
“…Li et al reported a phase-inversion method that allowed the growth of ZIF-8 on the surface of electrospun polyacrylonitrile (PAN) nanofibers to be used for CO 2 capture. 208 ZIF-8 was solvothermally synthesized by mixing zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O) and 2-methyl imidazole (2-mim) for 1 h at room temperature; complete physical and chemical analysis of the resulting structures is shown in Table 3. PAN nanofibers were immersed in Zn(NO 3 ) 2 ·6H 2 O for 20 min, and then 2-mim were added and left to react for 30, 60, and 90 min, leading to formation of ZIF-8/PAN-30, ZIF-8/PAN-60, and ZIF-8/PAN-90, respectively.…”
Section: Applications Of Framework For Co2 Detectionmentioning
confidence: 99%
“…Recently, advanced nanostructuring of zeolite and MOF adsorbents into hierarchical porous nanobers has been investigated for energy and environmental applications, including biogas separation and storage. [29][30][31][32] Zhang et al fabricated hierarchical porous ZSM-5 nanocomposite pellets for CO 2 separation from a biogas stream, which revealed a 30% increase in specic BET surface area, a 34% increase in CO 2 adsorption capacity as compared to ZSM-5 nanopowder. Apart from the high CO 2 uptake capacity, these structured pellets with 46% porosity displayed a high mass transfer coefficient of 1.24 m s −1 in the adsorption column.…”
Section: Introductionmentioning
confidence: 99%
“…The zeolitic imidazolate framework (ZIF) has been extensively used for CO 2 adsorption due to its structural diversity and performance superiority. 17 In addition, ZIF has significant disadvantages as opposed to advantages, such as expensive material preparation, poor thermal and chemical stability, and other issues. The other absorbents like activated carbon (AC) 18 have better surface area compared to the other adsorbents, and they have their own limitations such as less thermal stability at higher temperatures, which leads to certain limitations in CO 2 adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The selective adsorption of CO 2 at a lower temperature is mainly due to the presence of unsaturated metal cations available in the framework structure of MOF. , Still, the adsorption is limited compared to the other adsorbents, and their industrial applications are also restricted due to their poor chemical and thermal stability, low availability, and expensive cost. The zeolitic imidazolate framework (ZIF) has been extensively used for CO 2 adsorption due to its structural diversity and performance superiority . In addition, ZIF has significant disadvantages as opposed to advantages, such as expensive material preparation, poor thermal and chemical stability, and other issues.…”
Section: Introductionmentioning
confidence: 99%